Effectiveness of a coordinated ambulatory care program for patients with mental disorders or multiple sclerosis: results of a prospective non-randomized controlled trial in South Germany - Seeralan, Tharanya; Magaard, Julia L.; Engels, Alexander; Meister, Ramona; Kriston, Levente; Liebherz, Sarah; König, Hans-Helmut; Härter, Martin (Frontiers in Psychiatry, 2023)
Background The Psychiatry, Neurology, Psychosomatics and Psychotherapy (PNP) program of the German statutory health insurance AOK BW promotes coordinated and evidence-based specialist care with the aim of providing individualized, guideline-based outpatient care, strengthening the collaboration between health care providers, as well as reducing care costs. The purpose of this study was to evaluate its effectiveness regarding patient-reported outcomes compared to the less specialized general practitioner program (GP) and usual care (UC). Materials and methods AOK insured patients, who were on sick leave due to a mental disorder (affective disorder, anxiety disorder, adjustment disorder, somatoform disorder, alcohol abuse disorder, schizophrenia) or multiple sclerosis were included in the prospective non-randomized controlled study. All patients either participated in the PNP program (intervention group, IG-PNP), the general practitioner program (control group, CG-GP) or usual care (control group, CG-UC). Entropy balancing was used to adjust for baseline imbalance between groups. Primary outcome was health-related quality of life, assessed by the Short-form health survey (SF-36) 12 months after diagnosis. Secondary outcomes included symptom severity, functional health, and treatment satisfaction. Results Of the 14,483 insured patients who were contacted, 1,104 patients participated at baseline and 725 at follow-up. The adjusted mean differences of SF-36 sum score did not significantly differ between groups: −1.89 (95%-CI = −4.60; 0.81, p = 0.170) between IG-PNP and CG-GP, and −1.42 (95%-CI = −4.05; 1.22, p = 0.293) between PNP and CG-UC. The adjusted mean differences of secondary outcomes did not differ between groups, except for a slightly higher increase of functional health in CG-UC. Conclusion We found no evidence that the PNP program is superior to the GP program or to usual care in terms of patient-reported outcomes or treatment satisfaction. The results are limited by the low response rate. Accordingly, future studies should strive for more representative samples. To improve the program, an integration of further collaborative care elements and guideline recommendations might be useful. Clinical trial registration DRKS (German Clinical Trials Register https://drks.de/search/en); identifier (DRKS00013114).